PERAN BUDAYA ORGANISASI DALAM MENGINTERNALISASI NILAI-NILAI ISLAM PADA SISWA DI LEMBAGA PENDIDIKAN ISLAM - Farid, Miftah; Nugraha, Mulyawan Safwandy (Ibn Khaldun University, Bogor, 2024)
Organizational culture is the foundation that shapes the way work is conducted, interactions, and the values upheld by an organization. In this regard, the organizational culture in Islamic educational institutions must reflect these religious values. A strong organizational culture aligned with Islamic principles is believed to create an environment that supports the intellectual and spiritual growth of students, as well as fosters character development based on Islamic teachings. This research is a qualitative study conducted at Madrasah Aliyah Negeri 2 in Bandung in September 2024. Data collection techniques were carried out through interviews, observations, and documentation using Miles and Huberman's model of analysis through data reduction, data display, and drawing/verification. The results of this study indicate that the organizational culture at MAN 2 Bandung plays a crucial role in internalizing Islamic values among students, providing a strong foundation for the development of Islamic character. Teaching and learning activities, as well as routine religious activities such as a 15-minute recitation of the Qur'an before classes, congregational prayers, and Qur'an comprehension activities, serve as examples of organizational culture artifacts that not only reflect the institution's commitment to shaping Islamic behavior in students.